SOME GUIDELINES FOR CONDUCTING RESEARCH IN APPLIED BEHAVIORAL PHARMACOLOGY. Issue 2 (20th May 2013) - van Haaren, Frans; Weeden, Marc
Abstract The Journal of Applied Behavior Analysis (JABA) has published a number of articles on the behavioral effects of psychomotor stimulant drugs in individuals with attention deficit hyperactivity disorder. Some additional JABA publications have included investigations of the behavioral effects of other drugs. However, a review of these articles revealed many methodological differences among studies, which makes it difficult to evaluate the relative contribution of each research effort to the overall database. In this context, we offer some guidelines to solidify the methodological rigor of behavior pharmacological research published in JABA.